Demographic Changes, Labor Supplies, Labor Complementarities, Calendar Annual Wages of Age Groups, and Cohort Life Wage Incomes - Bjarne S. Jensen; Peder J. Pedersen; Ross Guest (Institute of Labor Economics (IZA), 2022)
This paper analyzes the impact on age group wage differentials in a setting of imperfect labor substitution at different ages (years) of working life. We examine the wage prospect of assuming medium, high, and low levels of fertility during the population projection period (2020-2090). Main focus is on comparisons of selected Calendar year Age wage profiles and the comparisons of selected Cohort Lifetime wage profiles. The analytical results come from applying a CRESH Labor Aggregator to Age-group Labor supplies with a parametric calibration to register based micro data for Denmark. The results show Calendar year wage effects and Cohort wage effects from ageing that will not exist without non-zero Labor Complementarity elasticities, and are new contributions demonstrating the economic effects of large/small generations and cohort sizes. The impact of cohort size on the lifetime wage profile of its own cohort does depend on sizes of other cohorts, which are affected by the fertility rates underlying many cohorts. Hence, economic advantages of being a small cohort depend on fertilities and the sizes of many other existing cohorts.
Keywords: J1; O4; E2; 330; labor substitution; CRESH; demographic cohorts; lifetime wage incomes